457 Survey of Perceived Barriers to Medical Students for Progression into Surgery. (4th May 2021) - Toh, S; Jayawardena, O; Fowler, H; Fok, M; Clifford, R
Abstract: Introduction: Applications for surgical training have been decreasing despite higher numbers of medical school graduates. We sought to explore the perceived barriers to medical students for progression into surgery. Method: An online anonymised SurveyMonkey® questionnaire aimed at medical students was disseminated in May 2020, with survey invitations advertised through social media. Results: A total of 271 responses were obtained, with 95% of respondents being undergraduates and a 7:3 female to male ratio. Approximately one-fifth (19%) were considering pursuing a career in surgery. 82% of students had observed in an operating theatre. 54% of respondents agreed that their surgical rotation was a positive experience, 21% neutral, 8% negative. Most frequent perceived barriers included lack of work-life balance (77%), surgical culture (67%), lengthy post-graduate training pathway (63%), and competitive entry of surgical specialties (63%). Others included a lack of understanding of surgical career pathways (52%), limited exposure to surgery (47%), and lack of interest (37%). Notably, gender bias was a barrier for many (35%). Most wanted more exposure to surgery through surgical skills teaching (85%), theatre experience (67%), surgical placements (59%) and didactic teaching (33%). Conclusions: Modifiable barriers need to be addressed in undergraduate and postgraduate training to boost the number of applications into surgical training.